Drug delivery options and therapeutic advances in the management of erectile dysfunction. (1st September 2020) - Grice, P.T.; Liu, J.; Gabrielson, A.T.; Pearce, I; Bivalacqua, T.J.; Modgil, V.
ABSTRACT: Introduction: Erectile dysfunction (ED) is defined as the inability to achieve or maintain an erection sufficient for satisfactory sexual performance. It is estimated that 20–30% of adult men will have at least one episode of ED during their lifetime and the prevalence increases with age. ED is known to have significant negative psychological implications for men, resulting in impaired functional status and a greater prevalence of anxiety and depression. Areas covered: Medications for the treatment of erectile dysfunction largely revolve around oral, injection, and topical therapies. Though all three modalities are widely used, each delivery option has its own advantages and specific indications. Likewise, there are several new developing treatments for ED that may change the landscape of treatment. The goal of this review is to summarize contemporary drug delivery options used in the treatment of ED and highlight future promising pharmacological developments. Expert opinion: There are a myriad of new developments on the horizon including new PDE5Is and drug targets, nanotechnology enhancements, stem cell and gene therapy, shockwave therapy, and platelet-rich plasma injections. These are all promising new methods to not only treat ED but also to address the pathology and prevent or eliminate further damage.